Biological activities of imidazo[2,1-b][1,3,4]thiadiazole derivatives: A review - Bhoomendra A. Bhongade; Sirajunisa Talath; Ravikiran A. Gadad; Andanappa K. Gadad (Journal of Saudi Chemical Society, 2016)
Imidazo[2,1-b][1,3,4]thiadiazole heterocycle was discovered during the 1950s. Since then, many newer derivatives are being developed and evaluated for their biological profiles. The derivatives of imidazo[2,1-b][1,3,4]thiadiazoles are widely explored for their biological potential viz. antimicrobial, antifungal, anticancer, anticonvulsant, analgesic, antiinflammatory, anesthetic, and diuretic. They are also reported as potential enzyme inhibitors of cyclooxygenase, Jun kinase, carbonic anhydrase demonstrating their possible significance in target oriented drug design and discovery. The present review highlights the last six decades of research on biological activities of the imidazo[2,1-b][1,3,4]thiadiazoles.